Digital Dilemmas Transforming Gender Identities and Power Relations in Everyday Life - Parry, Diana C.; Johnson, Corey W.; Fullagar, Simone (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
The proliferation of digital technologies, virtual spaces, and new forms of engagement raise key questions about the changing nature of gender relations and identities within democratic societies. This book offers a unique collection of chapters that brings together scholars from diverse backgrounds to explore how gender experiences and identities are being transformed by digital technologies in ways that affirm or deny social justice. .